Character education and the rise of mental health in Muhammadiyah Boarding School - Rahmah Hidayati; Arif Rahman; Zalik Nuryana; Yusutria Yusutria (Intelektual Pustaka Media Utama, 2022)
This study aimed to determine various characters implemented at modern Islamic Muhammadiyah Boarding School (MBS). This school is in Pleret, Bantul, Special Region of Yogyakarta, Indonesia. This research was a case study. The researcher carefully investigated a program, event, activity, process, or individual whose case is time-limited, and activity is determined by using a qualitative approach. The data were analyzed using descriptive analysis. The researcher has analyzed the research based on data obtained from interviews, observation, and documentation. The characters implemented at MBS are religious character, independence, social character, team building, and ta’zim (RISTA). Implementing these character values benefits students' mental health, resulting in strong Islamic personalities and good mental health MBS graduates.